PEMANFAATAN BIOMASSA LAMUN ENHALUS ACROIDES SEBAGAI BIOSORBEN ION LOGAM Cu(II) - Lestiyanti, Deasy; ., Muliadi (Green Earth, 2012)
Biosorption, representing alternative technique which can be used to overcome environmental contamination which come from waste discard of heavy metals pollutant. Biosorption of Cu(II) ion by biomass of seagrassi Enhalus acroides with variation of contact time, pH and concentration was investigated. The concentration of Cu(II) ion before and after adsorption was determined by atomic absorption spectrophotometer (AAS). pH optimum in biosorption process was conducted at pH of 1 â 7. Results showed that the optimum contact time was 60 minute and and the optimum pH was 6, respectively. Biosorption of Cu(II) ion by biomass of seagrass Enhalus acroides conducted at various concentration to study the isoterm adsorption. Models of isoterm adsorption used were Langmuir and Freundlich isoterms. Results showed that biosorption of Cu(II) ion by biomass of seagrass Enhalus acroides according to Freundlich isoterms with the biosorption capacity value (k) 0,6100 mg/g.Â Key words: AAS; Langmuir isoterm; Enhalus acroides, Biomass, Biosorption.